Peran Pemerintah dalam Mengendalikan Tingkat Daya Saing Kelompok Petani di Bolaang Mongondow Sulawesi Utara - Rifky Pakaya; Arinny Astary Gobel; Firka Manggo; Abdul Latif (Global Leadership Organizational Research in Management, 2024)
The role of government in agriculture is very important in determining economic policy, in planning to mobilize actors there must be readiness, seriousness and commitment to implement it. In an effort to establish regional autonomy, readiness to face future challenges and effective and efficient management of the regional economy by utilizing regional potential and resources. support that has a comprehensive design is needed, in order to obtain information that is in accordance with the problem formulation and research objectives. The method used in this research is a qualitative descriptive research method. This research is located in Bolaang Mongondow district (North Sulawesi). Regarding the role of the government in controlling the level of competitiveness of farmer groups in Bolaang Mongondow district (North Sulawesi). Data collection methods This research uses secondary data. The role of the government as a regulator is that the government prepares the implementation of development (issuing regulations in the framework of the effectiveness and orderliness of development administration). capital through providing capital assistance to the community. The government as a catalyst, the village government has a position as an agent that accelerates the development of village potential. The research results show that the government's role in controlling the level of competitiveness of farmer groups in Bolaang Mongondow, North Sulawesi, is very important and has a positive impact. With support and assistance from the government, farmers can increase their productivity, expand markets, and increase their income.